Willingness to participate analysis of urban waste management in West Sumatra, Indonesia - Idris Idris; Dewi Zaini Putri; Zul Azhar; Joan Martha; Isra Yeni (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Waste management shares the same purposes with the Sustainable Development Goals (SDGs) target in 2030. This program encourages all countries to substantially reduce waste through prevention, reduction, recycling, and reuse its waste so that the sustainability of development can be achieved. The success rate of sustainable waste management is largely determined by the participation and behavior of people, households, and citizens in managing their waste. This study analyzes socio-economic factors and the role of social capital in affecting households' willingness to participate in waste management in West Sumatra’s urban areas. This study used National Socio-Economic Survey data in the Social Resilience module. The sample in this study is 1011 households spread across the urban areas of West Sumatra. Using logistic regression, this study found that per capita household expenditure, homeownership status, knowledge, and household involvement in mutual cooperation activities to clean up their environment significantly affect the probability of households participating in urban waste management. The relevant policy, such as implementing the 3R concept, namely reduce, reuse, and recycling is needed for the Sustainable Development Goals to be achieved.